Momentum life cycle around the world - LI, Frank Weikai (Institutional Knowledge at Singapore Management University, 2015)
The momentum life cycle (MLC) hypothesis first proposed by Lee and Swaminathan (2000) applies also to global markets. Early-stage strategies significantly outperform the late-stage and conventional strategies in most countries. Individualism culture is positively associated with late-stage but unrelated to early-stage momentum profitability, suggesting that early- and late-stage momentums are driven by different underlying mechanisms. Consistent with Stein’s (2009) model that arbitrageurs could amplify mispricing, we find that late-stage momentum profits are more pronounced in countries with lower limits to arbitrage. Furthermore, we find that the MLC also applies to exchange traded funds in the United States.